Nyabek Toloh; Traditional Bid in Madura Culture a review of Sociology of Islamic Law) - Yayan Sopyan; Muhammad Shofwan Nidzami (Universitas Islam Negeri Jakarta, 2018)
Indonesia is a country built on the pillars of diversity, in terms of ethnicity, culture, custom, and religion. Indonesian society is also known as a religious society, with religious values in various aspects of life. However, Indonesia is not a religious country, nor a secular country. If for Indonesians, religion is not their main purpose, then, it is a part of their life.There has been a smooth cohesion between religion and tradition in Indonesia. One of the examples is the tradition of Nyabek Toloh in Madura, which is a marriage proposal tradition. This paper examines the practice of nyabek toloh in Romben Guna village, Dungkek Region, Sumenep-Madura. The purposes of nyabek toloh are to symbolize the establishment of a relationship between the family of a male and female fiancé; to show the responsibility of a man to a woman by giving toloh; to maintain man’s dignity, and to maintain the tradition of sangkolan (elders). Conducting nyabek toloh is a must in abhakalan (marriage proposal); the absence of nyabek toloh will lead to the cancellation of abhakalan.